Religious actors and conflict transformation in Southeast Asia Indonesia and the Philippines - Rüland, Jürgen 1953-; Lübke, Christian von; Baumann, Marcel M. 1975- (Routledge contemporary Southeast Asia series, 2019)
"Drawing on a rich body of multimethod field research, this book examines the ways in which Indonesian and Philippine religious actors have contributed to conflict resolution and under what conditions these efforts have been met with success or limited success. The book addresses two central questions: In what ways, and to what extent, have post-conflict peacebuilding activities of Christian churches contributed to conflict transformation in Mindanao (Philippines) and Maluku (Indonesia)? And to what extent have these church-based efforts been affected by specific economic, political or social contexts? Based on extensive fieldwork, the study operates with a nested, multi-dimensional and multi-layered methodological concept which combines qualitative and quantitative methods. Major findings are that church-based peace activities do matter, that they have higher approval rates than state projects and that they have fostered interreligious understanding. Through innovative analysis, this book fills a lacuna in the study of ethno-religious conflicts. Informed by the novel Comparative Area Studies (CAS) approach, this book is strictly comparative, includes in-case and cross-case comparisons and bridges disciplinary research with Area Studies. It will be of interest to academics in the fields of conflict and peacebuilding studies, interreligious dialogue, Southeast Asian Studies and Asian Politics"--